Risk factors of cardiovascular evens in primary care patiens - Główczyńska, Renata; Pietrasik, Arkadiusz; Starczewska, Marta E.; Filipiak, Krzysztof J.; Opolski, Grzegorz (Przewodnik Lekarza/Guide for GPs, 2005)
This work presents epidemiological data from survey called Standard of Primary Cardiac Care (SPOK) realized among national program of prevention and treatment of cardiovascular diseases (POLKARD). The study was run on patients at high risk of cardiovascular events. Among them there were patients at high 10-year risk of cardiovascular death according to Systematic Coronary Risk Evaluation (SCORE). Survey data were collected from representative group of 950 randomly selected, primary care physicians (poz). The study was obtained on 19 593 patients registered at primary health care system. Nearly 72% of patients were diagnosed for coronary artery disease and 28.9% of patients had history of previous myocardial infarction. There was high evidence of modificable risk factors of cardiovascular diseases.